Hyperbranched Microwire Networks of Organic Cocrystals with Optical Waveguiding and Light‐Harvesting Abilities. (23rd November 2021) - Feng, Zuofang; Hai, Tao; Liang, Yin; Zhang, Qing; Lei, Yilong
Abstract: We report the synthesis of hyperbranched organic microwire (MW) networks comprising 1, 4‐bis(pentafluorostyryl)benzene (10Ft) and 9, 10‐bis(phenylethynyl)anthracene (BA) using a simple solution co‐assembly route. Pure 10Ft or BA assemblies cannot produce such complex MW networks; in contrast with a binary cocrystal of 10Ft and BA with a 2:1 molar ratio ((2:1)10Ft:BA), which is formed via intermolecular arene‐perfluoroarene (AP) interactions. A new generation of multiple MWs grow epitaxially on the previous generation of MWs to form MW arrays in which BA may also act as an intermediate product to facilitate the regeneration of (2:1)10Ft:BA. Highly aligned and well‐connected MW networks enable superior optical waveguiding ability. Moreover, a red‐emitting dopant, 5, 12‐bis(phenylethynyl)naphthacene (BN) was incorporated into (2:1)10Ft:BA host MWs, giving light‐harvesting hierarchical MW networks via an energy‐transfer (ET) process. The realization of the hyperbranched MWs provides us with deep insight into the rational creation of complex branched arrays from functional organic cocrystals. Abstract : Hierarchical micro‐ and nanostructures made of π‐conjugated molecules are not yet reported due to the weak control over intermolecular interactions and little‐known complex assembly behavior of organic species. Hyperbranched microwire networks comprising binary organic arene‐perfluoroarene cocrystals were created, which show optical waveguiding and light‐harvesting abilities.